Dinamika Program Siaran TVRI Tahun 1969-1989 - Nafi, Anan Tawazzun; Alamsyah, Alamsyah (Sabda: Jurnal Kajian Kebudayaan, 2023)
During the New Order era, economic development policies were the focus of the Soeharto administration. To implement development, the country's socio-political conditions needed to be controlled. This control was done through the utilisation of television as a tool to spread development messages. This mass media is very effective and efficient in shaping people's mindset. In carrying out its duties, TVRI does so through its broadcast programmes. However, people do not like TVRI's lighting broadcasts, they prefer entertainment broadcasts. Therefore, development messages began to be inserted into TVRI's entertainment broadcasts. This effort intensified after advertising was banned on television. At that time, almost all TVRI broadcasts were aimed at supporting development policies. This situation lasted until the New Order government collapsed.